Effects of building envelope surface area and insulation thickness on heating cost - Aksoy, U. Teoman; Keleşo?lu, Ömer (My University, 2007)
In this study, the energy losses from opaque parts of building envelope are investigated according to surface area, building orientation stated and insulation thickness. Time-dependent one dimensional heat transfer is assumed to exist in external walls and an expilicit finite difference method is used in the solution of conduction heat transfer problem of the external walls. Calculations were done with the climatic data of Elazi?, where is one of the coldest cities of Turkey. According to heat losses calculated for a building which has long sides oriented to east-west and short sides to north-south, the maximum amount of heat losses occurs in east-west direction because of the large of the surface area in this directions. Energy savings with amount of 19%-77% provided depending on insulation thickness. Payback period of lost energy based on insulation cost is 5.3 and 13.6 years.
Bi?na kabu?u yüzey alani ve yalitim kalinli?inin isitma mali?yeti? üzeri?nde etki?leri?
Keywords: Building envelope; Building orientation; Heating cost; Insulation thickness